Efeito da laserterapia de baixa intesidade comparada a terapia fotodinâmica com curcumina em pacientes com mucosite oral - Andrade, Rita de Cássia Dias Viana (2019)
The objective of this study was to evaluate the effectiveness of Low-Level Laser Therapy (LLLT), Photodynamic Therapy (PDT) mediated by curcumin, and blue light as adjuvant to the treatment of cancer patients undergoing chemotherapy and radiotherapy with oral mucositis. The randomized controlled clinical study was developed at UNACON of the General Hospital of Vitória da Conquista (HGVC). In the total, data were collected from 30 patients that fit the criteria of inclusion and exclusion. Inclusion criteria were: minimum age of 18 years, stable lesions in process of Chemotherapy (QT) and / or Radiotherapy (RT) and consent to participate in the study by signing the Free and Informed Consent Form. The exclusion criteria of the research were: patients who received medication for the treatment and prevention of mucositis and patients unable to comply with the treatment procedure or the oral hygiene protocol. Finally, the criteria for loss were: patients who leave their group by free decision during the study period, patients who modify the QT or RT protocols of cancer treatment, patients who have worsened ulcers and are, therefore, receiving medication specific for mucositis and patients hospitalized due to worsening of their oncological condition. Patients were divided into control group, who were treated with nystatin; LLLT group, treated with laser therapy; and PDT group, who were treated with blue light mediated by the photosensitizer curcumin. Samples of non-stimulated saliva were collected after 7, 14, 21 and 30 days of treatment initiation, before and after the section using sterile universal collectors for one minute, as well as the observation of pain level and mucositis degree of the patient. The collected material was stored in a refrigerated environment until the moment of the samples processing, respecting the maximum time of three hours between the collection and processing. An acute decrease in Candida ssp. yeast was observed in the PDT group when compared to the LLLT group during all four collections, and an intragroup reduction in the PDT and LLLT groups during the last two collections. A chronic decrease in Candida ssp. yeast was observed in the PDT and LLLT groups in relation to the control group from the third and fourth day of collection respectively, and no difference was found in any of the groups when compared intra group. Regarding the pain score, a reduction in LLLT and PDT groups was observed in relation to the control group after thirty days of treatment. An intragroup reduction of the pain score in the PDT group was observed after 14 days of treatment, in the LLLT group after 21 days of treatment and in the control group after 21, but with an increase after 30 days of treatment. Regarding the degree of mucositis of the control and PDT groups, there was an intragroup statistical difference throughout all the collections, and the control group presented an increase in the degree of mucositis from its 14th day of treatment, while the LLLT and PDT groups a reduction in the mucositis from the 30th and 21st days of treatment, respectively. From these results, we can conclude that curcumin-mediated antimicrobial PDT and LLLT are noninvasive modalities for the prevention and management of oral mucositis with some advantages such as antimicrobial effect, analgesic effect, and reduction of inflammation. However, in the antimicrobial PDT mediated by curcumin when compared to LLLT, greater reduction of yeasts of the genus Candida was observed. In addition, the mean creep of 20.1 J / cm2 irradiated by the LED associated with curcumin proved to be effective in the lethal sensitization of yeasts of the genus Candida.